Multimodal late fusion bag of features applied to scene detection - Lopes, Bruno Lorenço; Goularte, Rudinei (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2013: Proceedings of the 19th Brazilian Symposium on Multimedia and the Web, 2013)
Recent advances in technology have increased the availability of video data, creating a strong requirement for efficient systems to manage those materials. To make efficient use of video information, first, the data has to be automatic segmented into smaller, manageable and understandable units, like scenes. This paper presents a new, multimodal video scene segmentation technique. The proposed approach is to combine Bag of Features based techniques (visual and aural) in order to explore the latent semantic obtained by them in complementary way, improving scene segmentation. The results achieved showed to be promising.